Acceptability and accessibility of pre-exposure prophylaxis modalities for HIV prevention (oral daily PrEP, dapivirine vaginal ring and long-acting cabotegravir injectable) among female sex workers in Salt River, Cape Town : a cross-sectional study - Mbuyamba, Rachel (Stellenbosch : Stellenbosch University, 2022)
Thesis (MPhil)--Stellenbosch University, 2022.